ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY - Annurrizky Muflisha Anggradewi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to examine the impact of firm size,level of leverage, quality of public accountant firms, type of industry, and independence of the audit committee toward audit delay in companies that listed on Indonesia Stock Exchange. Sampling method that used is cluster random sampling were then selected by predetermined criteria and the result are 128 firms as sample. The data used are secondary data, namely the financial statements of companies listed on the Indonesia Stock Exchange in 2012. The data which have already collected are processed with classic assumption test before hypothesis test used multiple linear regression analysis. Research model passed the test of the classical assumptions. The result of this research shows that independent variables simultaneously influenced 11.3 percent of dependent variable. Partial testing results show that there are two of the five factors that influence audit delay, the quality of a public accountant firms and type of industry have negative influence.